Participatory Governance Driving Innovation in Public Policy Implementation - Jamil Bazarah (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes the role of participatory governance in driving public policy innovation, emphasizing collaborative mechanisms between the government and citizens in Samarinda City. Using a qualitative case study approach, the research involved eight key informants— government officials, community leaders, academics, and civil society representatives— selected through purposive sampling. Data were gathered through participatory observation, indepth interviews, and policy document analysis, and examined using thematic analysis. The findings show that participatory governance significantly fosters policy innovation by enhancing transparency, cross-sector collaboration, and public accountability, although challenges persist in bureaucratic capacity and sustaining citizen engagement. The study concludes that participatory governance is a crucial catalyst for innovative, inclusive, and community-oriented public policy, contributing both theoretically to the collaborative governance paradigm and practically to improved policy development.